2016
DOI: 10.5603/gp.2016.0062
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer in young women

Abstract: Breast cancer (BC) in young women is rare, affecting only 4-6% of women under the age of 40. Regardless, BC remains the most common malignancy among younger patients. Recently, a significant increase in BC rates has been observed among pre-menopausal subjects. Breast cancer in young women requires special attention due to its specific morphologic and prognostic characteristics and unique aspects, including fertility preservation and psychosocial issues (e.g. its impact on family life and career). Young women a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
69
1
16

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(112 citation statements)
references
References 25 publications
(31 reference statements)
8
69
1
16
Order By: Relevance
“…Younger women usually searched for the support needed to fulfill their desire to become pregnant after cancer therapy (Hsieh et al., ; Quinn et al., ; Radecka & Litwiniuk, ; Ruddy et al., ). Similarly, we found that young women had stronger intentions to conceive.…”
Section: Discussionmentioning
confidence: 99%
“…Younger women usually searched for the support needed to fulfill their desire to become pregnant after cancer therapy (Hsieh et al., ; Quinn et al., ; Radecka & Litwiniuk, ; Ruddy et al., ). Similarly, we found that young women had stronger intentions to conceive.…”
Section: Discussionmentioning
confidence: 99%
“…As young women tend to have more biologically aggressive cancer, they are also more likely to elect for mastectomy and contralateral prophylactic mastectomy (CPM) . Overall, young breast cancer patients have inferior prognoses versus older women with the disease, and studies have shown that young age is a strong risk factor for breast cancer mortality . Racial and socioeconomic factors further compound these disparities.…”
Section: Introductionmentioning
confidence: 99%
“…young breast cancer patients have inferior prognoses versus older women with the disease, and studies have shown that young age is a strong risk factor for breast cancer mortality. [5][6][7] Racial and socioeconomic factors further compound these disparities.…”
mentioning
confidence: 99%
“…Studies from across the world have defined 'young patients' in case of breast cancer (BC), as women diagnosed with breast cancer before the age of 35 to 40 years. [3,4] Studies from western world have shown that young patients account from 2 to 5% of all breast cancer population. [5,6,7] Name & Address of Corresponding Author Dr. Arundhati Consultant Pathologist, Mahavir Cancer Sansthan and Research Institute, Patna…”
Section: Introductionmentioning
confidence: 99%